The Circadian Code: Deciphering the Role of Blood Groups in Sleep Pattern - Warsi, Jamshed; Noor, Naila; Ansari, Shafaq; Uddin, Syed Farhan (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To establish the relationship between blood groups and sleep, establish the interference that differences in blood groups have on circadian rhythms, and specifically establish and analyze sleep patterns among blood groups. Methods A cross-sectional study was conducted in the Department of Physiology from March 2023 to June 2023, with a sample size of 381 male participants within the age range of 18–24 years. Blood grouping was performed, and a valid questionnaire (PSQI) was employed to determine the quality of sleep. Results Among 381 participants, 118 (30.97%) were having good sleep and 263 (69.03%) were suffering from bad sleep. According to the PSQI questionnaire, 54 (14.17%), 114 (29.92%), 32 (8.39%), and 63 (16.53%) were in the A, B, AB, and O blood groups, respectively, and had bad sleep. Furthermore, 234 (61.41%) and 29 (7.61%) were in the in the Rh+ and Rh-blood groups, respectively, and had bad sleep. The highest frequency of bad sleep was found in B+ blood group 105 (27.55%). Conclusion Conclusively the highest frequency of bad sleep was found in blood group B and RH+.